Tax Avoidance by Business Entities: A Legal Analysis Under Indonesian Tax Law - Rizal Wahyudi; Gilang Rizki Aji Putra (SALAM: Jurnal Sosial dan Budaya Syar-i, 2026)
Tax avoidance represents a persistent challenge in revenue administration, creating tension between corporate financial optimization and state revenue mobilization. This study examines the legal dimensions of tax avoidance practices by business entities within the Indonesian taxation framework. Employing a normative juridical methodology with a qualitative descriptive approach, the research analyzes statutory provisions, particularly Law No. 28 of 2007 on General Provisions and Tax Procedures, Law No. 36 of 2008 on Income Tax, and Law No. 40 of 2007 on Limited Liability Companies. The findings reveal that Indonesian tax law distinguishes between lawful tax avoidance, which exploits regulatory loopholes without violating statutory provisions, and unlawful tax evasion, which involves fraudulent acts such as financial statement manipulation. Business entities, as tax subjects possessing Taxpayer Identification Numbers, bear mandatory obligations to pay Income Tax and Value-Added Tax under the self-assessment system. The study identifies passive and active forms of tax resistance, with active resistance further categorized into avoidance, evasion, and negligence. While tax avoidance operates within legal boundaries, the absence of bona fide business purpose may render certain transactions illegitimate, particularly concerning multinational corporate structures. The research contributes to the theoretical understanding of the legal boundary between permissible tax planning and impermissible tax evasion, offering practical implications for tax administrators, corporate taxpayers, and legislative reform efforts. Limitations include the exclusive reliance on secondary data and the normative scope of analysis, suggesting future empirical investigations into enforcement patterns and corporate compliance behavior. Keywords: Tax Avoidance, Tax Evasion, Business Entities, Indonesian Tax Law, Corporate Taxation, Self-Assessment System, Tax Compliance